A self-calibration method with high-accuracy and low-cost for large-area motion stage based on digital grating projection mode. (30th October 2019) - Huang, Shengzhou; Li, Mujun; Wang, Lei; Su, Yongsheng; Liang, Yi
Abstract: We report a self-calibration method with high-accuracy and low-cost for large-area motion stage. A programmable digital grating projection mode based on digital micromirror device was proposed, which can effectively avoid defocusing problem of calibration system and complete a stable high-accuracy calibration. Instead of adopting the high-cost laser interferometer measurement system, a self-calibration method based on reverse strategy was developed, which can easily obtain an optimal positional accuracy. This presented method can be expected to provide a new route for developing various applications such as laser direct writing equipment, automated optical inspection equipment.